Penegakan Hukum Mengenai Kasus Adanya Pemungutan Retribusi Tempat Parkir Di Mini Market - Silvia Rosiana; Arini Saarah; Mulyadi Mulyadi (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
Indomaret and alfamart are franchise minimarket chains in Indonesia. This minimarket provides a variety of basic necessities and daily necessities. Indomaret and Alfamart are very easy to find in residential areas, office buildings and public facilities. Law enforcement is aimed at improving order and legal certainty in society. This is done, among others, by regulating the functions, duties and authorities of institutions in charge of enforcing the law according to the proportion of their respective scopes, and is based on a good cooperation system and supports the goals to be achieved. Parking is a stop that is also one of the public facilities that can be used by anyone while traveling, parking lots are very important for temporarily store your vehicles such as motorbikes and cars when you are going to activities. The practice of illegal levies is rife once implemented. The form that is easiest to find is what often occurs in various public places, where we often find irresponsible people who ask for parking money illegally. This action is clearly troubling because it is contrary to regulations in the place which actually does not charge parking fees to visitors. Hereby the case is regulated in the Law, Article 1 number 64 of Law No. 28 of 2009 mentions the issue of parking levies which are payments for certain services or permits provided specifically or given from local governments as in the interest of private persons or entities. So that this parking attendant can be subject to extortion and threats in articles 368-371 of the Criminal Code is part of Chapter XXIII of the Criminal Code which contains "Whoever, with intent to benefit himself or others by contravening rights, coerces a person by force, threats of violence, so that that person gives goods, which wholly or partly include the person's own property to another person or so that the person makes a debt or write off receivables, punishable for extortion with imprisonment for not more than nine years. In regional regulation Number 03 of 2011 concerning Regional Taxes in Chapter III Article 69 Number 1 which reads "Tax Collection is prohibited from being bought"